El Excentrico, 1965-11-05 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
November 5, 1965[5 de noviembre de 1965]. Ano 16, No 2. Cover has a picture of government officials signing documents, with headline, "Organizations present grievances and demands to Anti- Poverty Commision."